2017
DOI: 10.1097/nne.0000000000000394
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring Nontenured Track Nursing Faculty

Abstract: The purpose of this systematic review was to evaluate the effectiveness of mentoring strategies for nursing faculty progression and productivity in the nontenure track at institutions of higher education. Sixty articles were included in the review. Findings revealed that nontenure track nursing faculty require planned programs and mentoring strategies unique to their role and abilities. Schools of nursing can improve on faculty progression, scholarship, and career growth by providing structured mentoring activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Although formal United States mentoring programs in schools of nursing are not widespread, interest in their integration is increasing 19 . However, formal mentoring programs within midwifery education is limited.…”
Section: Current Mentoring Programs In the United Statesmentioning
confidence: 99%
“…Although formal United States mentoring programs in schools of nursing are not widespread, interest in their integration is increasing 19 . However, formal mentoring programs within midwifery education is limited.…”
Section: Current Mentoring Programs In the United Statesmentioning
confidence: 99%
“…22 A study of nontenure-track nursing faculty presented similar recommendations. 23 Although these studies did not specifically examine gender, they both suggested that formal mentoring programs can help faculty achieve promotion despite being on a nontenure track. Our focus group data suggest that lack of mentoring for women can be a barrier to promotion, so formal mentoring or coaching programs at the institutional level are one potential way that promotion disparities could be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…To realise this, it is imperative to define clinical entry criteria, models for career progression and develop bridges between the faculty and clinical settings (Baltruks & Callaghan, 2018 ). Also, careful investments should be made to support PhD‐prepared nurses by means of orientation into the academic work by developing supportive networks (Bryant et al, 2015 ; Rice et al, 2020 ), access to mentoring (Cullen et al, 2017 ; Hafsteinsdóttir et al, 2017 ; Nowell et al, 2017 ) and leadership and professional development programmes (Bryant et al, 2015 ; Rice et al, 2020 ; van Dongen et al, 2021 ). Although opportunities like these are more common in North America, some initiatives are taking place in European countries, like the Dutch Leadership Mentoring in Nursing Research Programme (Hafsteinsdóttir et al, 2020 ; van Dongen et al, 2021 ) and the European NurseLead programme, which acknowledge and take seriously the need to educate both doctoral nursing students and PhD‐prepared nurses in the wider range of competences to build sustainable careers in various areas of health care, education and academe (Hafsteinsdóttir et al, 2017 ).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Mentoring by experienced doctorally prepared nurses as well as support by colleagues and peers was found to support leadership and career development of doctorally prepared nurses. Mentoring supported them in their academic work, strengthened academic skills and supported them in developing an academic identity (Al‐Nawafleh et al, 2013 ; Cullen et al, 2017 ; Hafsteinsdóttir et al, 2017 ; Nowell et al, 2017 ). However, to this day, only a limited number of doctorally prepared nurses has access to these resources (McKenna, 2021 ).…”
Section: Introductionmentioning
confidence: 99%